PUBLIC-PRIVATE PARTNERSHIPS IN THE PROVISION OF HOUSING IN GAUTENG - Mazibuko, Hanson Mbuso (My University, 2011)
PPPs have become increasingly used in the provision of goods and services historically considered the primary responsibility of the state because they are vital for human survival. These include goods and services such as housing, water and health services- all globally recognised as basic human rights. The introduction of PPPs has in many ways changed the role and character of the state for example from being the key provider of goods and services to that of regulator, a situation that may have ramifications for the protection and fulfilment of these and other basic human rights. Therefore, this study set out to investigate the implications of PPPs on the provision of housing as a human right and public good. Using two case studies in Gauteng, South Africa, and the study found that PPPs have both positives and negatives. Positives include effective mobilisation of scarce resources like land, expertise, funds and project management skills. However, due to the need by private partners to recover costs and earn profits this makes housing unaffordable for the poorest urban dwellers, thus perpetuating homelessness, poverty and marginalisation. Overall, this has a negative impact on poor people‟s right of access to adequate housing
MM thesis - P&DM
Keywords: Public-private partnerships; Housing